DESIGN AND IMPLEMENTATION OF SOFT BODY MODEL FOR CHILDBIRTH SIMULATION - MURDYANTORO A.M. (NIM: 23207137), EKO
ABSTRACT: Development of simulation in virtual reality canÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â’t be separated from the objects that can be deformed both its shape and volume, such as the soft body. Like in the childbirth simulator ParSIM, its applied soft body modeling with a mass-spring method. This method is physically based deformable object that is compute the force at the entirely elements. In order to get the a realistic visualization modeling, it is necessary to determine the value of soft body parameters such as mass, damping coefficients and spring stiffness. The childbirth process is a very complex system. In the implementation of the graphical modeling and simulation system, the childbirth process can not be entirely applied in ideal conditions. Main issues, among other considerations limit the complexity to be applied to more affordable, as well as the limitation of soft body implementation with mass-spring system. Therefore can not be avoided a simplification of the system still retains the nature of the simulation. This research has produced an applicable simulation system approach and soft body modeling that is applied on the childbirth simulator ParSIM.